Risk Factors of Pregnant Women with Anemia for LBW Incidence in Maospati, Indonesia - Sri Wahyuni Pudjianti; Budi Joko Santosa; Nani Surtinah; Sunarto Sunarto (Knowledge Dynamics, 2024)
Background: The prevalence of low birth weight (LBW), according to the World Health Organization (WHO), is estimated to be 15%–20% of all births worldwide. Babies with LBW face a challenging and risky life trajectory, often experiencing growth and development disorders. Pregnant women with a history of anemia are considered a risk factor for LBW cases. This study aims to determine the risk factors for anemia in pregnant women and the incidence of LBW in the Maospati Community Health Center area. Methods: This observational analytic study employed a case-control design. The case population consisted of LBW infants, while the control population included non-LBW infants. The case sample comprised 25 LBW infants, and the control sample included 50 infants who were not LBW. The independent variable was the history of anemia in pregnant women, and the dependent variable was the incidence of LBW. Data were collected from medical records and labor recapitulation records from February 2023 to February 2024, using an observation sheet as the research instrument. Data analysis involved calculating the proportion of cases to exposure and determining the odds ratio. Results: The study found a significant association between a history of anemia in pregnant women and the incidence of LBW in their babies, with a p-value of 0.003. Pregnant women with anemia had a 4.571 times greater risk of giving birth to an LBW baby compared to those without anemia. Conclusions: The findings indicate that a history of anemia in pregnant women is a significant risk factor for LBW in newborns. Monitoring pregnancy and hemoglobin levels is essential to reduce the incidence of LBW in infants.